Developing a Dissemination Model to Improve Intervention Reach among West Virginia Youth Smokers - Horn, Kimberly; Jarrett, Traci; Anesetti-Rothermel, Andrew; O’Hara Tompkins, Nancy; Dino, Geri (Frontiers in Public Health, 2014)
The not-on-tobacco program is an evidence-based teen smoking cessation program adopted by the American Lung Association (ALA). Although widely disseminated nationally via ALA Master Trainers, in recent years, adoption and implementation of the N-O-T program in West Virginia (WV) has slowed. WV, unfortunately, has one of the highest smoking rates in the US. Although it is a goal of public health science, dissemination of evidence-based interventions is woefully understudied. The present manuscript reviews a theoretical model of dissemination of the not-on-tobacco program in WV. Based on social marketing, diffusion of innovations, and social cognitive theories, the nine-phase model incorporates elements of infrastructure development, accountability, training, delivery, incentives, and communication. The model components as well as preliminary lessons learned from initial implementation are discussed.